1980-ականների վերջին և 1990-ականների սկզբին լիբանանյան աջ ուժերի ճակատում հակասությունների սրման հարցի շուրջ - Հարությունյան, Լիլիթ («Զանգակ - 97»)
In the late 1980's and in the early 1990's the struggle for the hegemony and the deepening of contradictions between different right forces inside the "Lebanese Front" (headed by Samir Geagea) leaded to the "Lebanese Front's" disunification. In this process the sensible role played also the subscription of Taif Agreement (signed in September 22, 1989), as well as General Michel Aoun's (one of the influential leaders of the "Lebanese Right Forces Front") negative attitude towards Taifs theses. Michel Aoun optimally tried to use his objections conccming Taif Agreement in favour of the confirmation of his own rule not only in "Lebanese Front", but also in whole Lebanon. In his struggle as a unificalion factor General Aoun used unti-Syrian slogans.
Keywords: Պատմություն; Քաղաքականություն